Countering elevated CO2 induced Fe and Zn reduction in Arabidopsis seeds. Issue 5 (24th June 2022) - Sun, Peng; Isner, Jean‐Charles; Coupel‐Ledru, Aude; Zhang, Qi; Pridgeon, Ashley J.; He, Yaqian; Menguer, Paloma K.; Miller, Anthony J.; Sanders, Dale; Mcgrath, Steve P.; Noothong, Fonthip; Liang, Yun‐Kuan; et al.
Summary: Growth at increased concentrations of CO2 induces a reduction in seed zinc (Zn) and iron (Fe). Using Arabidopsis thaliana, we investigated whether this could be mitigated by reducing the elevated CO2 ‐induced decrease in transpiration. We used an infrared imaging‐based screen to isolate mutants in At1g08080 that encodes ALPHA CARBONIC ANHYDRASE 7 (ACA7). aca7 mutant alleles display wild‐type (WT) responses to abscisic acid (ABA) and light but are compromised in their response to elevated CO2 . ACA7 is expressed in guard cells. When aca7 mutants are grown at 1000 ppm CO2 they exhibit higher transpiration and higher seed Fe and Zn content than WT grown under the same conditions. Our data show that by increasing transpiration it is possible to partially mitigate the reduction in seed Fe and Zn content when Arabidopsis is grown at elevated CO2 .